Evaluating microbiological quality of kitchen equipment in school canteens / Rosnaini P. Ramli ... [et al.] - P. Ramli, Rosnaini; Salman, Hanis Syakira; Sazari, Lea Nursuria Sariza; Azmi, Alia (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Food preparation requires constant safety and health supervision and careful handling of raw materials. Due to the nature of processes occurring during food preparation, equipment within any food establishment will come into contact with various types of microbiological organism. If cleanliness is not ensured, equipment such as dishwashing sponges and cutleries can be a source of contamination, leading to foodborne diseases. This is a serious health hazard, especially if it occurs within a setting that has vulnerable populations, such as a school canteen. As such, this study aims to evaluate the microbiological quality of kitchen equipment in school canteens, as well as the effectiveness of the cleaning agents used in the kitchen. Carried out in three schools in Puncak Alam, microbiological swabs were obtained from sponges, cutleries and plates used in each of the school canteen. Based on the microbiological analysis, Salmonella was detected the highest (mean; 4 log10 cfu/ml), compared to E. coli (mean; 3.4 log10 cfu/ml) and S.aureus, which showed the least growth (mean; 2.05 log10 cfu/ml).